Caesarean Section of Multifetal Pregnancy - Tanigaki, Shinji; Takemori, Satoshi; Osaka, Makoto; Watanabe, Momoe; Kitamura, Aya; Ueyama, Sayaka; Tanaka, Kei; Matsushima, Miho; Kobayashi, Youichi (The Surgery Journal, 2020)
Planned caesarean delivery (CD) did not significantly decrease or increase the risk of fetal or neonatal death or serious neonatal morbidity in twin pregnancy between 32 0/7 and 38 6/7 weeks of gestation, with the first twin in the vertex presentation. As prevalence rises for the second twin, emergency CD is necessary for delivery of the second twin after vaginal delivery of the first twin. Waiting after 38 weeks' gestation essentially requires close fetal and maternal surveillance to identify if those pregnancies may benefit to extend a gestational period. It is important to construct a system in which an emergency CD can be performed anytime. The caesarean section does not change in even multifetal pregnancy. Each step after laparotomy has few tips: (1) because the uterus strongly leans to the right, image the uterine rotation. To avoid thick vessels on the uterine lateral wall, perform long U-shaped incision using a scissor. 2) Ensure not to rupture the membrane of the second twin before delivery of the first twin. (3) Check the presentation of the second twin before rupture of that fetus's membrane. The second twin tends to change the presentation. If the upper uterine segment will clamp down and entrap the second twin, a vertical uterine incision is performed without hesitation. Women with multifetal pregnancy are at increased risk of postpartum hemorrhage (PPH). Mainly PPH is caused by uterine atony. Oxytocin should be prepared before starting the CD. All bleeding may not be recognized in the operation field. Do not lose the timing of blood transfusion.
Keywords: multifetal pregnancy; twin pregnancy; caesarean section; postpartum hemorrhage